Introduction to water quality modeling - Vishnuradhan, Renjith; Zainudin, Zaki; Vethamony, P (Institution of Engineers Malaysia, 2012)
In recent years water pollution control and water quality management strategies are gaining prominence in developed as well as developing countries in the wake of global environmental scenarios like resource depletion, climate shifts, population pressure and last not the least, increased public awareness. In spite of all the efforts taken by the research community and governmental agencies, water quality is deteriorating in many areas around the globe. Access to safe water is a basic human right. According to UNICEF, water related diseases caused by insufficient safe water supplies coupled with poor sanitation and hygiene cause 3.4 million deaths a year, mostly among children [1]. More stringent regulations are mandatory in keeping the water quality for its sustainable utilization, as water is one of the major players in a development perspective.